Meijiki niokeru shashin gainen to (shashintekina mono): shashin no shikakusei to mediasei konseputo o chūshin ni - Wakita, Mio (Kajima-bijutsu-zaidan-nenpō, 2012)
Meiji-concepts of photography and the photographic: Focusing on the visuality and mediality of photography